Endoscopic approaches for treating emphysema - Kontogianni, Konstantina; Eberhardt, Ralf (Expert review of respiratory medicine, 2018)
Surgical treatment of severe pulmonary emphysema has so far been associated with relatively high perioperative morbidity and mortality. In the past two decades, novel approaches to lung volume reduction and alternative minimally invasive endoscopic techniques have been developed. This review presents the different techniques (blocking and nonblocking) available until present as well as the appropriate patient selection and possible complications.